Zane Grey : His Life, His Adventures, His Women - Pauly, Thomas H. (Book collections on Project MUSE., 2005)
Zane Grey was a disappointed aspirant to major league baseball and an unhappy dentist when he belatedly decided to take up writing at the age of thirty. He went on to become the most successful American authors of the 1920s, a significant figure in the early development of the film industry, and vital to the early popularity of the western.